Existence and nonexistence results for generalized quasilinear Schrödinger equations of Kirchhoff type in ℝ3. Issue 14 (25th October 2020) - Shen, Liejun
ABSTRACT: This paper is concerned with the existence and nonexistence results for generalized quasilinear Kirchhoff-type equations in R 3 which have appeared from plasma physics, as well as high-power ultrashort laser in matter. By using a change of variables, we obtain the existence of solutions via Link argument, where a nonexistence result for a minimizing problem is also established by the Nehari–Pohoz˘aev manifold.